The effect of continuous training on myoglobin muscle and on some specific fitness elements and basic skills of badminton players - Al-Selmi, A. D. H.; Al-Shawi, S. S.; Mohammed, S. H. (Journal of Human Sport & Exercise, 2019)
The current study problem can be described in the form of the following question and the following sub-questions as follows: What is the effect of continuous training in Myoglobin muscle and on some of the special fitness elements and basic skills of badminton players? The following questions stem from this question:1. myoglobin level in muscles? 2. What is the level of some fitness elements for badminton players? 3. What is the basic skills level of badminton players?. The current research aims to prepare continuous training exercises for the research sample, to identify the effect of continuous training method in the level of muscle myoglobin in the development of certain elements of special fitness and basic skills of badminton players. Methodology: The researchers used the experimental approach in designing the one group with the tribal and remote tests. The research sample consisted of badminton players in the youth club of the At huri Club. The team consisted of (12) players, (2) player for the exploratory experiment, Explosive force (two men) Agility, Flexibility Technical tests Massive strike, front impact, rear strike.1. The researcher`s concluded.2. The results showed that the level of myoglobin in the muscles within the normal limits when using the method of continuous training of badminton players.3. Exercise according to the continuous training method has led to the development of some special fitness elements and basic skills of badminton players. Recommend the researchers: to circulate the results of the current study on the sports teams participating in the league in badminton.